Extending locked range of digital phase-locked loop by prediction estimation of states - ZHAO Yi-bo1; LUO Xiao-shu2; ZHANG Dao-yang3; FENG Jiu-chao1 (Tongxin xuebao)
A method to extend locked range of the positive zero crossing detection digital phase-locked loop（ZC-DPLL） was proposed.The nonlinear dynamical model of phase error of a non-controlled DPLL is firstly built,linearation predic-tion estimation of phase error in the stationary point domain is derived.Then nonlinear function of this prediction estima-tion is used to control by feedback.Locked range of the phase-locked loop is extended.Stability of fixed point of the controlled system is analyzed and the results by simulation are given.The effects not only show the proposed method is correct and effective but also it is superior to delay feedback method.